Model Deteksi Autis Secara Dini Berdasarkan Pendekatan Logika Fuzzy Inference System Metode Mamdani - Ahmad Al Kaafi - AMIK BSI Tegal (Bianglala Informatika, 2017)
ABSTRACT - Autism is a disorder in children who have speech and a different way of communicating with other children his age were caused by developmental abnormalities of the nervous system. The term autism was first introduced by Leo Kanner in 1943. It used to autism is considered to be a lifelong disorder that can not be handled, but today many are aware that the handling of the symptoms of autism as early as possible can bring remarkable changes impact on children's development who have it. To check whether a child has autism or not, to use international standards on autism. ICD-10 (International Classification of Diseases) in 1993 and DSM-IV (Diagnostic and Statistical Manual) in 1994 to formulate criteria for the diagnosis of Autism Infantil with the same content, which is currently used throughout the world. Fuzzy logic can be used in diagnosing autis early childhood. Fuzzy Inference System (FIS) is a model Mamdani Mamdani fuzzy reasoning system that can be applied in the process of diagnosing autis in children of various criteria for patient characteristics. Using a data processing application logic while Mamdani FIS decision support systems using MATLAB toolbox R2011b. The result of this study is to diagnose autis decision support early childhood Mamdani FIS approach is more precise and efficient.Keywords: Diagnoses Of Autism, Fuzzy Inference System MethodMamdani. ABSTRACT - Autism is a disorder in children who have speech and a different way of developmental abnormalities of the nervous system. The term autism was first introduced by Leo Kanner in 1943. It used to be autonomous as it is possible to bring a remarkable change impact on children's development who have it. To check whether a child has autism or not, to use international standards on autism. ICD-10 (International Classification of Diseases) in 1993 and DSM-IV (Diagnostic and Statistical Manual) in 1994 to formulate criteria for the diagnosis of Autism Infantil with the same content, which is currently used throughout the world. Fuzzy logic can be used in diagnosis autis early childhood. Fuzzy Inference System (FIS) is a model Mamdani Mamdani fuzzy reasoning system that can be applied in the process of diagnosing autism in children of various criteria for patient characteristics. Using a data processing application logic while MIS FIS decision support systems using MATLAB toolbox R2011b. The result of this study is to diagnose autism decision support early childhood Mamdani FIS approach is more precise and efficient.Keywords: Diagnoses Of Autism, Fuzzy Inference System MethodMamdani.